Application of Criminal Law in Online Gambling Case: (Case Study Decision No. 02/Pid.B/2022/PnPwk) - Wendi Darman Laia; Martono Anggustin; Lesson Sihotang (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This research discusses the application of criminal law in online gambling cases in Indonesia, with a focus on decision No. 02/Pid.B/2022/PnPwk. The development of information technology has led to the emergence of cybercrime, including online gambling, which has a negative impact on society. Through a normative research approach, this study analyzes the challenges faced in law enforcement related to cybercrime, as well as legal protection for victims. The results show that despite regulations such as the Electronic Information and Transaction Law (EIT Law), many provisions are considered ambiguous, resulting in legal uncertainty. Law enforcement is also hampered by a lack of technological understanding among law enforcement and limited international cooperation. Therefore, it is necessary to update regulations and increase technological capacity to strengthen efforts to handle online gambling in the digital era. This research is expected to provide insights for the development of legal policies that are more effective and responsive to the challenges of cybercrime.